Comunità di fan – Partecipazione e cultura pop negli She She Pop - Matzke, Mieke (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay is a critical presentation of the work of the She She Pop theater group, which originated in the context of university courses in theater studies, which turns its attention to themes, texts and formats of popular and everyday culture. The goal is an approximation of theater to what is perceived as contemporary social reality. The artists stage themselves and themselves as co-authors of texts that are found in reality. They reject the idea of the playwright as a single author of dialogic texts to be staged and, in general, the idea of staging a drama understood as a presentation of a reading of the text by the director. The starting point of theatrical practice is no longer the dramatic, canonized text, but the set of fragments of popular culture texts – whether pop songs, advertising texts, television formats or popular myths – found in everyday culture. The word “pop” thus comes to define a perspective in which everything everything appears as material for theater, without any hierarchy.